Presentation - Editors (Farol, 2025)
It is with great pleasure that we present issue 32 of Farol, a publication that consolidates its position as a vital platform for interdisciplinary reflections on the arts, architecture, urbanism, and political philosophy. This issue, rich in thematic and geographic diversity, offers a thought-provoking overview of contemporary concerns, inviting readers to delve into urgent debates on collective identity, public space, memory, and the complex relationships between society and the environment.